1998
DOI: 10.2135/cropsci1998.0011183x003800040026x
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and Sediment Losses from Natural and Man‐Made Erosion Control Materials

Abstract: Man‐made erosion control materials are increasingly being used at construction sites. The performance of these materials in comparison to natural materials is largely unknown. A rainfall simulation study was designed in which four man‐made materials (wood excelsior, jute fabric, coconut fiber blanket, and coconut strand mat) and two natural materials (straw and turfgrass sod) were evaluated. The erosion control materials were evaluated on a Sassafras loamy sand (fine loamy, mixed mesic Typic Hapludult) having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 0 publications
2
30
1
Order By: Relevance
“…As noted for Experiment 1, our runoff time was longer and sediment loss was lower than observed in other studies [26] [27] probably due to small slopes in our study.…”
Section: Experiments 2 321 Rainfall Simulationsupporting
confidence: 62%
See 1 more Smart Citation
“…As noted for Experiment 1, our runoff time was longer and sediment loss was lower than observed in other studies [26] [27] probably due to small slopes in our study.…”
Section: Experiments 2 321 Rainfall Simulationsupporting
confidence: 62%
“…Time to runoff for grass generally ranges from 2 to 15 min [26] [27]. Sediment loss from grass can range from 10 to 180 kg·ha −1 over 35 min [26], or from 0.1 to 104 kg·ha −1 per event of 12 to 30 min duration [28].…”
Section: Second Rainfall Simulationmentioning
confidence: 99%
“…That site also had no sediment loss in the third year, whereas all other sites had some sediment loss. Time to runoff was generally lower than most values (2 to 78 min) in the literature [30,32,33].…”
Section: Resultscontrasting
confidence: 67%
“…Similarly, Hytiris et al (2001) documented the case of a poorly secured synthetic geomat on a flume bed detaching, and this induced increased velocity in the boundary region. In a rainfall simulation study, Krenitsky et al (1998) found that an OW coir product (DeKoWe-700 similar to one of the RECSs tested in this study, i.e. 705 g m 2 ) was less effective than a jute or excelsior system.…”
Section: Index Property Differences Between Rolled System Groupsmentioning
confidence: 56%